2014
DOI: 10.1037/a0035231
|View full text |Cite
|
Sign up to set email alerts
|

Developmental change in proactive interference across the life span: Evidence from two working memory tasks.

Abstract: Working memory (WM) as the ability to temporarily maintain and manipulate various kinds of information is known to be affected by proactive interference (PI) from previously relevant contents, but studies on developmental changes in the susceptibility to PI are scarce. In the present study, we investigated life span development of item-specific PI. To this end, 92 individuals between the ages of 8 and 74 years completed a recent-probes task and an n-back task that both composed experimental manipulations of PI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 64 publications
3
30
1
3
Order By: Relevance
“…Recent-probes task: The recent-probes task (cf. Monsell, 1978) has previously been used to assess PI-processes within WM (see Jonides and Nee, 2006;Unsworth, 2010) and was adapted from Loosli et al (2014). Twelve animal pictures (non-colored line drawings) from the Snodgrass and Vanderwart object collection (Snodgrass and Vanderwart, 1980) were used as stimuli (see Figure 1A).…”
Section: Experimental Tasks and Design T R A I N I N G T A S K Smentioning
confidence: 99%
See 3 more Smart Citations
“…Recent-probes task: The recent-probes task (cf. Monsell, 1978) has previously been used to assess PI-processes within WM (see Jonides and Nee, 2006;Unsworth, 2010) and was adapted from Loosli et al (2014). Twelve animal pictures (non-colored line drawings) from the Snodgrass and Vanderwart object collection (Snodgrass and Vanderwart, 1980) were used as stimuli (see Figure 1A).…”
Section: Experimental Tasks and Design T R A I N I N G T A S K Smentioning
confidence: 99%
“…N-back task: The visual two-back task was adapted from Loosli et al (2014). Twelve pictures of daily objects (non-colored line-drawings, from Cycowicz et al, 1997; see also Snodgrass and Vanderwart, 1980) were used as stimuli (see Figure 1B).…”
Section: Experimental Tasks and Design T R A I N I N G T A S K Smentioning
confidence: 99%
See 2 more Smart Citations
“…In the non-numerical domain, it has repeatedly been observed that older adults have more difficulty resolving proactive interference in memory tasks (e.g., Chiappe, Siegel, & Hasher, 2000;Jonides et al, 2000;Loosli, Rahm, Unterrainer, Weiller, & Kaller, 2014;May, Hasher, & Kane, 1999;Thompson-Schill et al, 2002). For instance, Jonides et al (2000) compared age-related changes in proactive interference via the recent probes task (Monsell, 1978).…”
Section: Introductionmentioning
confidence: 99%